SEJARAH PESANTREN DI INDONESIA: : Sebuah Pelacakan Genealogis - Abdurrahman Abdurrahman (Jurnal Penelitian Ilmiah INTAJ, 2020)
Some research states that the earliest pesantren established in Indonesia since the 13th century in Sumatra and the 15th century in Java. In Sumatra it was marked by the progress of the Lamreh Kingdom in the Barus area, while in Java it was marked by the existence of Wali Singo. However, if we examine the history of the existence of Islam in the archipelago, which is believed since the beginning of Islam in the 7th century, it is necessary to trace the possibility of the formation of pesantren before the 13th century. With this method, the author succeeded in formulating 4 indicators of the possibility of the formation of pesantren, namely sima land as a special area of ??religious institutions, figures with high-level terms and books that are familiar among the population, progress of the Islamic empire and extensive Islamization, and indications of pesantren genealogy from some other terms. From these 4 indications, pesantren existed since the 10th century in Leran Manyar Gresik village